Análise das linhas de financiamento e o custo do capital das MPEs sergipanas - Nascimento, Herbert Menezes do (2010)
The small business are fundamental economic and social importance for the Brazilian economy, because they generate jobs and income. It is observed that such companies are important for Brazil, although they do not receive adequate treatment, except those who benefit from the services provided by SEBRAE, and the state banks, with minimal participation, not existing Therefore, the financial market, a greater concern and attention to their basic needs supply of capital in volume and level of fees, provision of guidance or support to business management. Thus, this study sought to identify, from a multiple case study, the main sources of financing used by micro and small entrepreneurs in Sergipe and the cost of capital provided by several financial institutions operating in the market. To collect the primary data were interviews with the main manager in eight small companies that operate in the state of Sergipe. Secondary data were collected from information from the Central Bank of Brazil and analyze the portfolio of the lines offered by various financial institutions operating in the market Sergipe. From the data analysis, we determined that the lack of knowledge of managers of small businesses is a key determinant for inadequate use of existing funding lines on the market, reflecting the increased cost of capital. It was also possible to identify, from the perception of managers, the deficiency of banking service for small businesses, particularly the public banks.